The Local Governance of Arrival in Leipzig: Housing of Asylum-Seeking Persons as a Contested Field - Werner, Franziska (2018)
The article examines how the German city of Leipzig governs the housing of asylum seekers. Leipzig was a frontrunner in organizing the decentralized accommodation of asylum seekers when adopting its accommodation concept in 2012. This concept aimed at integrating asylum-seeking persons in the regular housing market at an early stage of arrival. However, since then, the city of Leipzig faces more and more challenges in implementing the concept. This is particularly due to the increasingly tight situation on the housing market while the number of people seeking protection increased and partly due to discriminating and xenophobic attitudes on the side of house owners and managers. Therefore, we argue that the so-called refugee crisis of 2015–2016 has to be seen in close interaction with a growing general housing shortage in Leipzig like in many other large European cities. Furthermore, we understand the municipal governing of housing as a contested field regarding its entanglement of diverse federal levels and policy scales, the diversity of stakeholders involved, and its dynamic change over the last years. We analyze this contested field set against the current context of arrival and dynamic urban growth on a local level. Based on empirical qualitative research that was conducted by us in 2016, Leipzig’s local specifics will be investigated under the umbrella of our conceptual framework of Governance of Arrival. The issues of a strained housing market and the integration of asylum seekers in it do not apply only to Leipzig, but shed light on similar developments in other European Cities.